Estudo do processo de tratamento de resíduos sólidos orgânicos do restaurante universitário da UFPB - Campus I - Andrade, Rômulo Wilker Neri de (2015)
Anaerobic digestion is a process of biological treatment of organic matter under microbial action in biodigesters. The absence of oxygen allows the production of biogas, a mixture composed of methane (CH4) and carbon dioxide (CO2), through a process composed of four phases: hydrolysis, acidogenesis, acetogenesis and methanogenesis. The objective of this work was to study the anaerobic digestion process in the treatment of solid organic wastes of the University Restaurant (UR) of the Federal University of Paraíba (UFPB) - campus I, in laboratory scale. The methodology followed a line of studies that was initially organized by the diagnosis, collection and characterization of the organic solid waste (OSW) of the UFPB - campus I; And anaerobic sludge from effluent treatment plant (ETP) Mangabeira, João Pessoa-PB, and Federal Institute of Paraíba (IFPB) - Cabedelo campus, which were used as inoculants; Starting and monitoring of experimental reactors; And treatment of the data obtained. The samples were incubated, following the Biochemical Methane Potential (BMP) test, in glass bottles with lid and septum, hermetically sealed. Three assays were performed and all were maintained at 35±5°C for 90 days in an incubator without agitation, with periodic monitoring of temperature, pressure and humidity. The potential of the inoculum in its wet and dehydrated aspect was studied. In addition, it was decided to add glucose in some reactors. At 60 and 90 days, the reactors were removed for the physical and chemical characterization of the degraded medium. The Organic Fraction of Urban Solid Waste (OFUSW) presented 51,8% of in-nature residues, and pH within the acidity range, 3.8 and 5.5. The inoculums tested showed organic matter loading of 18,1±2,6; pH between 6,8 and 7,8 and water content, between 92 and 99,8%, results that fit the process. At 90 days, some reactors presented mass losses, those composed by OSW and fresh anaerobic sludge from ETP Mangabeira, RSOLF (test I), RSOLG (test II) and RSOLGETE (test III), lost 2,95g, 55g and 1,52g, respectively. It was observed that glucose in the reactor composition was shown to be useful for the initial feeding and development of the bacteria. From the biogas production curves of the reactors with glucose in the three tests, it can be observed that the reactors that had the fresh sludge, as inoculum in their composition, produced more gases during the period of the research. Samples from trial III, RSOLETE and RSOLGETE, presented the best values of methane production, with 43,55% and 30,98%, respectively, at 90° day. Thus, the BMP test proved to be efficient in the treatment of organic solid waste and biogas production, and it was possible to observe a larger biogas production in the reactors that had sludge from the anaerobic lagoon of the ETP Mangabeira as inoculum.